An interface damage model for high-cycle fatigue. (November 2019) - Geng, F.; Suiker, A.S.J.
Highlights: The fatigue model simulates fracture in a computationally efficient way. The model accounts for mixed-mode loading conditions and fatigue loading of variable amplitude. The model is able to simulate fatigue cracking characterized by arbitrary cracking paths. The fatigue response computed for a single lap joint agrees well with experimental data. Abstract: A fatigue interface damage model is presented that is based on combining a fatigue evolution law with a static interface damage model. The fatigue model elegantly enables the simulation of crack initiation and propagation in a computationally efficient and accurate way, accounting for mixed-mode loading conditions and fatigue loading of variable amplitude. The basic features of the fatigue model are explained by means of the response of an isotropic mode I specimen. In addition, the fatigue response of a fiber-epoxy specimen is analyzed, thereby illustrating the effects by load cycle blocks of different amplitude and the generation of plasticity on the fatigue life of the specimen. Finally, the fatigue response of a single lap joint is computed, showing that both the number of load cycles to failure and the evolution of local deformation correspond very well with experimental data reported in the literature.